2008
DOI: 10.1021/bp0340180
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Evaluation of Producing Ethanol from Softwood: Comparison of SSF and SHF and Identification of Bottlenecks

Abstract: The aim of the study was to evaluate, from a technical and economic standpoint, the enzymatic processes involved in the production of fuel ethanol from softwood. Two base case configurations, one based on simultaneous saccharification and fermentation (SSF) and one based on separate hydrolysis and fermentation (SHF), were evaluated and compared. The process conditions selected were based mainly on laboratory data, and the processes were simulated by use of Aspen plus. The capital costs were estimated using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
305
0
10

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 575 publications
(321 citation statements)
references
References 24 publications
6
305
0
10
Order By: Relevance
“…Ethanol production by FBP-SSF at 20% solid could produce ethanol of 35.76 g/L or 4.6% (v/v), which was close to benchmark level (above 4.0% (v/v)). This may be economically viable to produce in large scale [5,16,17]. The result showed that ethanol production by FBP-SSF was a good manner for cellulosic ethanol production.…”
Section: Effect Of Commercial Cellulase Enzymes On Ethanol Productionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ethanol production by FBP-SSF at 20% solid could produce ethanol of 35.76 g/L or 4.6% (v/v), which was close to benchmark level (above 4.0% (v/v)). This may be economically viable to produce in large scale [5,16,17]. The result showed that ethanol production by FBP-SSF was a good manner for cellulosic ethanol production.…”
Section: Effect Of Commercial Cellulase Enzymes On Ethanol Productionmentioning
confidence: 95%
“…Zhu et al [15] used liquefaction at 50 °C for 120 h before ethanol production by SSF. Although it could give high ethanol concentration over the benchmark level (above 4.0% (v/v)) [5,16,17], it might be economically viable to produce in large scale. However, almost of material pretreatment was used in high severity condition, especially high temperature, such as Chu et al [9] pretreated corn stover at 190 °C for 3 min, Zhu et al [15] pretreated aspen at 170 °C for 10 min, and Albuquerque-Wanderley et al [18] pretreated sugarcane bagasse at 200 °C for 7 min.…”
Section: Effect Of Commercial Cellulase Enzymes On Ethanol Productionmentioning
confidence: 99%
“…A critical economical issue for the enzymatic hydrolysis of lignocellulosic biomass is the final glucose concentration. It has been stated that the ethanol concentration in the broth entering distillation should be greater than 40 g L -1 (Wingren et al, 2003). Assuming an ethanol yield of 0.48 g(g G) -1 , a G concentration of at least 83 g L -1 would be required to reach this target.…”
Section: Results Inmentioning
confidence: 99%
“…However, solids loadings higher than 10% w/w are required to obtain cost-effective concentrations of sugars (Wingren et al, 2003). Due to the high water-holding capacity of solids, the reaction medium cannot be efficiently sheared and mixed at solids loadings higher than 10% w/w (Viamajala et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Harvest/N/K feedstock production system [37][38][39][40][41][42][43][44]. This range in biorefinery willingness to pay for feedstock is much lower than what will be required by farmers to grow switchgrass as a dedicated feedstock crop on their farms.…”
Section: Pricesmentioning
confidence: 99%